In vitro methods for rabies virus detection, and evaluation of their use in the production of rabies immunoglobulin - Yu. K. Gavrilova; S. V. Generalov; E. G. Abramova; A. K. Nikiforov (Биопрепараты: Профилактика, диагностика, лечение, 2021)
Current highly sensitive methods for rabies virus and rabies antibodies detection in biological material can be used not only for diagnosis and experimental research, but also for the production of antirabies medicines used for postexposure prophylaxis. The aim of the study was to analyse existing methods for rabies virus and rabies antibodies detection and to assess the potential for using these methods at the control stages during production of heterologous antirabies immunoglobulin obtained from equine serum. The search for cutting-edge highly sensitive in vitro control methods that could compete with the biological method, which is the main method used in antirabies immunoglobulin control, is an important prerequisite for improvement of the production technology and the quality of antirabies medicines. The study demonstrated that the following test methods can be used in the production of antirabies immunoglobulin: fluorescent antibody technique, enzyme-linked immunosorbent assay, cell culture methods, atomic force microscopy, and flow cytometry. These methods could be used alone or as an alternative to the biological method in white mice. These methods were chosen because of their high sensitivity, specificity, rapid and easy implementation, cost-effectiveness, and automatic recording of test results.